Metal sulfides and their lithium storage properties - Liu, Weiling (2017)
Lithium ion battery (LIB) is currently one of the most widely used forms of rechargeable energy storage system in portable electronics. To achieve LIB with enhanced lithium storage properties, better safety aspects and lower cost, extensive research has been conducted on the various components of a LIB for the past few decades. Although graphite is currently used as the anode material in most commercial LIB, its limited capacity and the safety issues related to its low electrochemical potential (vs. Li/Li+) have prompted scientists to search for alternative materials. Amongst the various conversion-typed materials, metal sulfides are particularly interesting as sulfur (S) has a rich and versatile chemistry, thus providing the possibility of altering the lithium storage properties of the materials by simply varying the stoichiometric ratio between the metal and sulfide ion in the compound. However, as with all sulfur and sulfide electrodes, polysulfides will be formed during their partial reduction, resulting in poor capacity retention and cycling performance in lithium and lithium ion batteries. In view of this, more study needs to be carried out to find approaches that can be undertaken to improve the lithium storage performance of metal sulfide electrodes. Hence, this thesis aims to gain an insight into how the amount of sulfide ion in the stoichiometry of a metal sulfide compound affects its lithium storage properties, with the focus placed on two metal sulfide systems, namely, iron sulfides (intercalation-conversion material) and tin sulfides (conversion-alloying material).